Atlantic salmon Salmo salar passing a natural barrier before and after construction of a hydroelectric station. Issue 5 (4th September 2019) - Kennedy, Richard James; O'Connor, William; Allen, Michelle
Abstract: A hydro power plant constructed around a waterfall on a coastal spate river, used the fall as a natural fish pass and applied a previous telemetry study on local Atlantic salmon Salmo salar to determine the abstraction conditions for the site. The current study used the same telemetry approach to monitor the efficacy of S. salar passage and to compare migratory behaviour at the waterfall pre and post the hydro development. The probability of S. salar successfully crossing the waterfall was higher post‐hydro when 80% of tagged fish successfully crossed in comparison to the pristine pre‐hydro period when 44% of tagged fish ascended. The flow range used by tagged S. salar to cross the waterfall ranged from 2.49−7.87 m 3 s −1 in the pre‐hydro period but broadened to 1.32−12.91 m 3 s −1 during the post‐hydro period. This was principally due to the hydro diverting water away from the waterfall during spate conditions, damping the flow across the barrier and facilitating upstream migration within a more suitable discharge range. During 2017–2018 implementation of the hydro‐operation protocol elongated the duration of the migratory window for successful upstream migration by 36–128%. A strong diurnal pattern was observed for movements across the Salmon Leap waterfall during both the pre‐hydro and post‐hydro monitoring periods with most tagged S. salar crossing the complex obstacle in daylight.